2020
DOI: 10.1093/deafed/enz050
|View full text |Cite
|
Sign up to set email alerts
|

Language and Reading Progress of Young Deaf and Hard-of-Hearing Children

Abstract: We examined the language and reading progress of 336 young DHH children in kindergarten, first and second grades. Trained assessors tested children’s language, reading, and spoken and fingerspelled phonological awareness in the fall and spring of the school year. Children were divided into groups based on their auditory access and classroom communication: a spoken-only group (n = 101), a sign-only group (n = 131), and a bimodal group (n = 104). Overall, children showed delays in language and reading compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
1
40
0
1
Order By: Relevance
“…Discriminating Disorder From Delay/Difference At the group level, language skills in DHH children are often found to be, on average, between 1 and 2 standard deviations below those of test norms (which almost invariably represent monolingual children with typical hearing) or demographically matched hearing controls (Koehlinger et al, 2013;Tobey et al, 2013;Ambrose et al, 2014Ambrose et al, , 2015Tomblin et al, 2015;Eisenberg et al, 2016;Geers et al, 2017;Lewis et al, 2017;Hoffman et al, 2018;Lederberg et al, 2019;Antia et al, 2020). Of course, there is considerable heterogeneity at the individual level, and clinicians are charged with supporting one child at a time: assessing their current level of proficiency, making informed inferences about the reasons behind specific areas of weakness or strength, devising individualized interventions, and making recommendations to the child's family and the other allied professionals on the child's team.…”
Section: Language Input Matters At the Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Discriminating Disorder From Delay/Difference At the group level, language skills in DHH children are often found to be, on average, between 1 and 2 standard deviations below those of test norms (which almost invariably represent monolingual children with typical hearing) or demographically matched hearing controls (Koehlinger et al, 2013;Tobey et al, 2013;Ambrose et al, 2014Ambrose et al, , 2015Tomblin et al, 2015;Eisenberg et al, 2016;Geers et al, 2017;Lewis et al, 2017;Hoffman et al, 2018;Lederberg et al, 2019;Antia et al, 2020). Of course, there is considerable heterogeneity at the individual level, and clinicians are charged with supporting one child at a time: assessing their current level of proficiency, making informed inferences about the reasons behind specific areas of weakness or strength, devising individualized interventions, and making recommendations to the child's family and the other allied professionals on the child's team.…”
Section: Language Input Matters At the Individual Levelmentioning
confidence: 99%
“…The lack of true population-based datasets in the United States makes it difficult to know for certain, but large, multi-site/multi-state studies such as CDaCI, OCHL, and NECAP typically report language outcomes in DHH children that are 1-2 standard deviations below their hearing peers, or language quotients below the 80% threshold (Koehlinger et al, 2013;Tobey et al, 2013;Ambrose et al, 2014Ambrose et al, , 2015Tomblin et al, 2015;Eisenberg et al, 2016;Geers et al, 2017;Lewis et al, 2017;Hoffman et al, 2018;Yoshinaga-Itano et al, 2018). A separate and more recent study of over 336 DHH children between kindergarten and second grade reported similar outcomes on measures of spoken language, with mean scores again ranging from 1 to more than 2 standard deviations below the normative mean (Lederberg et al, 2019;Antia et al, 2020). These values are commensurate with the findings of a large, longitudinal, population-based study in Australia (LOCHI; see Ching et al, 2010Ching et al, , 2018 for language outcomes at age 3 and 5, respectively).…”
Section: Language Input Matters At a Population Levelmentioning
confidence: 99%
“…Although K-readiness may be considered predictive of academic success (eg, age-and/or gradeappropriate reading levels and high school graduation), 20,21 in children who are D/HH, K-readiness measures may not be sufficient predictors. Antia et al 47 noted average reading skills in kindergartners who were D/HH; by second grade, reading comprehension scores were nearly 2 SD below population norms. Other research has revealed that a high proportion of students consistently have reading skills below age-and grade-appropriate levels.…”
Section: K-readiness and D/hhmentioning
confidence: 97%
“…If phonology is important for reading, then deaf people should be at a disadvantage. Many people born deaf struggle to learn to read and do not reach a high level (Antia et al, 2020;Adlof et al, this volume). For those that do, phonology appears to be implicated.…”
Section: How Good Is Reading Without Phonology?mentioning
confidence: 99%
“…This finding suggests that the orthographic code alone may not be enough for fluent reading, even for people with hearing impairments (but see Costello et al, 2021, for a different view). Further evidence for a supporting role of phonology in deaf readers is the finding that phonological knowledge and exposure to speechreading predict reading skills in primary school children with hearing impairments (e.g., Antia et al, 2020;Harris et al, 2017). A remaining question is whether the phonology-based effects in deaf people come from spoken language (e.g., via speechreading) or can be based on sign language (e.g., Keck & Wolgemuth, 2020).…”
Section: How Good Is Reading Without Phonology?mentioning
confidence: 99%